Bioaugmentation of the anaerobic digestion of food waste by dungs of herbivore, carnivore, and omnivore zoo animals. Issue 4 (16th February 2018) - Ariunbaatar, Javkhlan; Ozcan, Onur; Bair, Robert; Esposito, Giovanni; Ball, Ray; Lens, Piet N.L.; Yeh, Daniel H.
ABSTRACT: The potential improvement of biomethanation of food waste (FW) by adding dung of herbivore (giraffe, llama, koala), carnivore (tiger), and omnivore (sloth bear) animals to anaerobic sludge (AnS) was investigated. Adding 30% giraffe, sloth bear or koala dung to the AnS inoculum yielded, respectively, a 11.17 (±4.51), 10.10 (±1.23), and 1.41 (±0.56)% higher biomethane production, as compared to the control (FW with solely AnS). The highest biomethane production of 564.00 (±3.88) ml CH4 /gVSadded obtained with 30% giraffe dung and 70% AnS was attributed to a higher solubilization of proteins (6.96 ± 2.76%) and recalcitrant carbohydrates (344.85 ± 54.31 mg/L as compared to zero). The biomethanation process could have been stimulated by the microorganisms or enzymes newly introduced, and/or the trace elements (Ni, Zn, and Co) present in the giraffe dung. These results indicate that bioaugmentation with zoo animals dung is worthy of further investigation as a strategy for improving the biomethane recovery from organic wastes.